EXPLORING SELF-REFLECTION PRACTICE AS A MEANS TO SELF-DEVELOPMENT FOR STUDENT TEACHER OF ELEMENTARY SCHOOL EDUCATION STUDY PROGRAM - Suryarini, Diah Yovita; Bahtiar, Reza Syehma (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2021)
This study aimed to investigate the self-reflection practice of prospective teacher of elementary education for their sense of self-development. This study will be guided by qualitative descriptive approach with phenomenology hermeneutics to investigate prospective teacher’s feeling in their written text. Accordingly the text would be analyzed using rhetorical analysis. The data of this study were collected from six written self-reflection that has correct composition as reflection from six prospective teacher that has taken implementation of thematic based learning class. The data of this study were analyzed based on its rhetorical expression with the consideration of the three stages of reflection process. The result of this study revealed that written self-reflections of prospective teacher mostly follow the same flow of reflection and has the sense of self-development in terms of their new perspective on the matter under consideration. Their new persepective usually in terms of conclusion or self-encouragement on the matter under consideration. The implication of this study was Result of this study may encourage the practice of reflection or self-reflection for prospective teacher so that it can be practiced and implemented more to the prospective teacher for their own personal and professional development.